Analisis Kandungan Zat Besi dan Kalsium Pada Biskuit dengan Penambahan Tepung Rumput Laut (Eucheuma cottonii) - Laili, Rizky D; Ethasari, Rossa K; Saidah, Qori Ila (Universitas Pattimura, 2023)
Seaweed is an eminent commodity of marine resources that has a complete nutritional content of both macronutrients and micronutrients, as well as polyunsaturated fatty acids. This study was conducted to determine the content of iron and calcium in cookies by adding seaweed as an alternative snack. This study was designed using 4 formulations: P1 (0% seaweed flour addition), P2 (10% seaweed flour addition), P3 (20% seaweed flour addition), and P4 (40% seaweed flour addition). This study used the complete randomized design method, which was then tested for iron and calcium content in seaweed cookies using the AAS method. Organoleptic tests were carried out to determine the most accepted formulation. The results showed that cookies with the addition of 20% seaweed flour have the most accepted organoleptic quality and have a fairly high iron content of 42 ppm and calcium content of 1458.28 ppm so they can be used as an alternative food high in iron and calcium and still have an acceptable taste.